Decision-Making Software-Integrated Ultrafast Detection of Lead in Surface Water Using a Chemo-Nano Sensing Device - Mahapatra S.; Chandra P. (My University, 2025)
Lead is highly toxic and commonly presents heavy metal ions in environmental samples. It can promote severe medical conditions involving nervous, cardiac, genital, and mental disorders due to exposure to even a minimal amount. Thus, fast and label-free lead ion (Pb2+) detection in natural sources such as water, agriculture, industrial, and medical samples is highly important. In this direction, in the following study, we have represented a nanochemo-tuned sensor system that can detect Pb2+ in water, even in the presence of other heavy metal ions. The sensor was electrochemically characterized and imposed to a self-reporting construct involving a flexible electronic chip. The sensor surface was engineered using highly conductive gold nanoparticles and metal complex nanohybrid. The promoter metal complex showed a coordinative ion exchange characteristic specific for Pb2+, further promoting the selective and robust detection of lead in the real water samples. The recorded limit of detection (LOD) was 1.72 (±0.01) nM (0.35 ppb) with a wide dual dynamic range of 0.006-0.25 μM (1.24-51.69 ppb) and 20-150 μM. The LOD is well within the limit set by the World Health Organization (WHO) (<10 ppb/0.048 μM) and the United States Environmental Protection Agency (EPA) (<15 ppb/0.072 μM) recommended for drinking water. The recovered concentration level of lead was found to be >90% in real water samples. The chip showed improved sensor robustness and reusability alongside an ultrafast response time of ≤1.0 s. An indigenously developed decision-making smartphone application has also been integrated into the sensor system. The software assists in the hassle-free detection of lead in water samples, supporting color-coded quality marking and storage of assessment history. © 2023 American Chemical Society.